2021
DOI: 10.1051/e3sconf/202128008020
|View full text |Cite
|
Sign up to set email alerts
|

Rock pressure relief is the basic alternative for sustainable underground mining

Abstract: Retreat longwall mining is the most productive system for underground extraction of tabulated deposits. However, the steady growth of the mining depth dramatically increased the ground pressure in chain pillars protecting the longwall entries. Therefore, several coal industries have tried to shift to pillarless mining and practiced maintenance of the head or tail entry behind the longwall in the stress relief zones using the backfill bodies in the thin coal seams. We modernized the pillarless variant of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Therefore, before the working face is laid out, the first step is to adopt a reasonable development layout and mining method to reduce the influence of geological formations on the working face [16,17]. Victor [18] modernised the pillarless system by introducing a third roadway as a pressure relief roadway to protect the working face roadway from the support pressure during mining of the adjacent slab. For the high stress area that has been formed, pressure relief should be conducted on any high stress areas, including coal seam blasting pressure relief, high-pressure water injection, and large diameter borehole pressure relief [19].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, before the working face is laid out, the first step is to adopt a reasonable development layout and mining method to reduce the influence of geological formations on the working face [16,17]. Victor [18] modernised the pillarless system by introducing a third roadway as a pressure relief roadway to protect the working face roadway from the support pressure during mining of the adjacent slab. For the high stress area that has been formed, pressure relief should be conducted on any high stress areas, including coal seam blasting pressure relief, high-pressure water injection, and large diameter borehole pressure relief [19].…”
Section: Introductionmentioning
confidence: 99%
“…From the two aspects of stress and energy, a reasonable pressure relief blasting scheme was put forward, which could transfer the concentrated high ground stress in the surrounding rock to the interior of the rock mass to reduce the risk of rock burst. Nazimko 22 used FLAC3D to study the effect of mining depth on the effectiveness of borehole pressure relief in the retreating longwall mining system and concluded that the extent of the stress relief zone was significantly enhanced after the use of backfill to modify the coalfree pillar variant of the longwall system. Wu 23 investigated the monitoring method of borehole pressure relief and proposed a neural network model based on single-sensor and multisensor prediction results, determining that the periodic amplification zones appearing in the vibration signals could characterize the depth of the borehole.…”
Section: Introductionmentioning
confidence: 99%